Mutual Comparison between the Two Computational Models of Interaction System Vehicle-Pavement - Valašková Veronika; Melcer Jozef (Transactions of the VŠB: Technical University of Ostrava, Civil Engineering Series, 2017)
Dynamic interaction between vehicle and pavement is a current problem which is solving in many workplaces around the world. This article is focused on the interaction model creation and principles of the solution for two numerical models. Numerical models of the interaction system vehicle-pavement were constructed in the computer software ADINA, which is based on the Finite Element Method.